2015
DOI: 10.1039/c4py01698j
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional ATRP based pH responsive polymeric nanoparticles for improved doxorubicin chemotherapy in breast cancer by proton sponge effect/endo-lysosomal escape

Abstract: Folic acid and trastuzumab functionalized pH responsive polymeric nanoparticles for intracellular doxorubicin delivery in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…2A clearly proved the formation of initiator, which was in agreement with above results in Fig. All these results 45 provided further evidence that poly(PEGMA) had been immobilized onto the surface of GCC NPs. The peaks of C1s with the binding energies at 285.5 and 284.5 eV corresponded to the sp3 and sp2 hybridized carbon atoms, while the peak at a higher binding energy of 287 eV was ascribed to the carbon atoms bound to oxygen (Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…2A clearly proved the formation of initiator, which was in agreement with above results in Fig. All these results 45 provided further evidence that poly(PEGMA) had been immobilized onto the surface of GCC NPs. The peaks of C1s with the binding energies at 285.5 and 284.5 eV corresponded to the sp3 and sp2 hybridized carbon atoms, while the peak at a higher binding energy of 287 eV was ascribed to the carbon atoms bound to oxygen (Fig.…”
supporting
confidence: 90%
“…6A-C, after four hours incubation with HeLa cells using GCC-poly(PEGMA) of 20 µg mL −1 , only weak fluorescence images of cells can be obtained, suggesting a small number of GCC-poly(PEGMA) being internalized. 45 The fluorescence stability of GCC-poly(PEGMA) in PBS was determined to be outstanding as shown in Fig. 6G-I).…”
Section: Cellular Imaging Of Gcc-poly(pegma)mentioning
confidence: 92%
See 1 more Smart Citation
“…It combined the proton sponge-mediated endo -lysosomal escape ability and dual targeting (flate and trastuzumab) had minimal cardiotoxicity, hepatotoxicity, and nephrotoxicity along with its high therapeutic efficacy. 312 Sun et al 313 reported two DOX functionalized prodrugs, one that was acid-sensitive ( cis -aconitic anhydride conjugated to PEG (CAD–PEG–CAD)) and the other was insensitive to pH changes (succinic anhydride conjugated to PEG (SAD–PEG–SAD)) which both self-assembled into micelles. Both micelles were stable at physiological pH ( i.e.…”
Section: Different Stimuli-responsive Mnpsmentioning
confidence: 99%
“…The day, on which treatment was begun, designated as a day zero and study was terminated on 21st day; tumor volume and weight of animal was measured alternatively. At the end of study, blood and vital body organs were collected and subjected to blood count, biomarkers analysis and histopathological examinations (Negi et al, 2014;Lale et al, 2015).…”
Section: In Vivo Antitumor Efficacy and Toxicological Studiesmentioning
confidence: 99%